Potentialités écologiques des carrières de quartzite après exploitation : l'exemple de la carrière de Cheffois (Vendée, France) - François Bétard (Physio-Géo)
In abandoned quarries of massive rocks, the aridity and oligotrophic character of soils, combined with the presence of rock walls and water bodies in the deeper excavations, are favourable to the expression of a renewed, original biodiversity. An ecological survey carried out on the quartzite quarry of Cheffois, located in the southern Armorican Massif, revealed the biological richness of this type of semi-natural environment. The results of our inventory have led to distinguish six types of neoformed habitats in old segments of the quarry: (1) a large water pit, (2) a wet tile zone, (3) a dry tile zone, (4) quarry faces with changing microclimatic conditions, (5) waste embankments, and (6) an underground cavity. These different sectors of the quarry are themselves divided into a mosaic of small habitats, promoting high biodiversity with the development of many plant and animal species, including some with high conservation value. Replaced into the geographic context of the Vendean "Bas-Bocage", the ecological contribution of the quartzite quarry is evaluated and tested against with losses in biodiversity caused by the opening of the extractive site. With other quartzite quarries located nearby, they together form a network of partially flooded quarries that could contribute to the creation of an ecological corridor, into a landscape matrix currently marked by losing biodiversity.